Structure for architects a case study in steel, wood, and reinforced concrete design - Bedi, Ashwani (Routledge, 2020)
This book focuses on structural principles applied to the design of typical structural members - a beam, a girder, and a column - in a diagrammatic frame building. Through the application of a single case study across three key materials, the book illustrates the theory, principles, and process of structural design. The case study progresses step-by-step for each material, from determining tributary areas and loads through a member's selection and design. The book addresses the frequent disparity between the way architects and engineers perceive and process information, with engineers focusing on technical aspects and architects focusing on visual concepts. Focusing on the conceptual understanding of structural design, this book will be of interest to architecture students and professionals looking to understand the application of structural principles in relation to steel, wood, and concrete design.